2016
DOI: 10.4236/wjcmp.2016.63025
|View full text |Cite
|
Sign up to set email alerts
|

Quenching Photoluminescence of Eu(III) by Cu(II) in ZnO:Eu3++Cu2+ Compounds by Solution Combustion Method

Abstract: In this study Cu 2+ +Eu 3+ co-doped ZnO(ZnO/Cu 2+ +Eu 3+ ) solid solution powders were synthesized by solution combustion method using as oxidant agent zinc nitrate hexahydrate and as fuel urea; the Cu 2+ concentrations were 0, 1, 2, 3, 10, and 20 %Wt; the Eu 3+ ion concentration was fixed in 3%Wt. The samples after were annealed at 900˚C by 20 h in air. The structural results showed the largely presence of a wurtzite solid solution of Cu 2+ +Eu 3+ doped ZnO, at high Cu 2+ doping CuO and Eu 2 CuO 4 phases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Auger process depends on the doping atoms concentration and defects in the lattice. [19]. However, in Fig.…”
Section: Photoluminescence Studymentioning
confidence: 87%
See 1 more Smart Citation
“…Auger process depends on the doping atoms concentration and defects in the lattice. [19]. However, in Fig.…”
Section: Photoluminescence Studymentioning
confidence: 87%
“…The ZnO has been co-doped with various elements (rare earth, lanthanides, metals, etc.) combined [2] can quench some emission photoluminescence type [19] as will be showed in this study. However, the doping of ZnO with Cu 2+ ions cannot modify ZnO structure [20].…”
Section: Introductionmentioning
confidence: 83%
“…There have been several reports on red luminescence from Eu 3+ ions in Eu-doped ZnO nanostructures including thin films, [10][11][12][13][14][15] nanocrystals [16][17][18][19] and nanorods/NWs. [20][21][22] We focus on ZnO NW structures as a host configuration to improve the crystal quality compared with conventional thinfilm configurations, and in this way increase the luminescence intensity.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate approach to producing luminescence with tailoring the light emission capabilities is to manipulate the matrix to control energy transfer [7,8]. Previous studies reported that luminescence quenching for Eu 3+ emission was obtained by doping Cu 2+ in ZnO [9] and glass matrix [10]. In particular, in our knowledge, there are no reports on the luminescence quenching for Eu 3+ / Cu 2+ doped ZrO2 nanoparticles.…”
Section: Introduction mentioning
confidence: 99%